Chest X-ray findings in COVID-19: A Pictorial Review - Nasir Khan ,Muhammad Umar ,Maria Khaliq ,Hina Hanif ,Misbah Durrani ,Riffat Raja (Journal of Rawalpindi Medical College, 2020)
Introduction: Chest X-ray and Computed tomography(CT) of chest play an important role in the diagnosis and management of the Coronavirus disease (COVID-19). As chest CT may not be readily available in most clinical setups X-ray Chest plays a pivotal role in such clinical scenarios and an irreplaceable initial radiological investigation of these patients. Objective: The objective of this article is to identify and elaborate the commonest appearances and patterns of lung changes on Chest X rays in COVID-19 positive patients confirmed on RT-PCR COVID testing. Materials and Methods: Cross-sectional descriptive-analytical study of Chest X-ray findings of 294 RT-PCR confirmed COVID-19 patients admitted across 3 hospitals (Rawalpindi institute of urology (RIU), Benazir Bhutto Hospital (BBH) and Holy Family Hospital (HFH)) from March 30th, 2020 till April 30th, 2020. CXR was analyzed for consolidation patches, ground-glass opacification (GGO), multi-lobe involvement, bilateral distribution, and pleural fluid. The chest X-ray with positive findings was graded into mild, moderate, and severe grades using BSTI (British Society of Thoracic imaging) guidelines. Results: Mean age of study patients was 45.5 years. Among the study population 230 (78.2 %) were male and 64 (21.8%) female. On baseline chest X rays, consolidations were the commonest finding (n=84, 28.5%), followed by ground-glass opacity (n=17, 5.7 %). The more common locations were peripheral and lower zones, and the majority had bilateral lung involvement (Table 1). Pleural effusions were found in only 5 of the study patients. Among these patients, 187 (63.6%) had an initial normal chest X-ray. Moreover, 35, 34, and 38patients had mild, moderate, and severe diseases respectively. Conclusion: Chest X-ray is an important initial radiological investigation for COVID 19 patients and plays an important role in the management during the course of the disease.